ABA activated SnRK2 kinases: an emerging role in plant growth and physiology. (31st December 2022) - Hasan, Md.Mahadi; Liu, Xu-Dong; Waseem, Muhammed; Guang-Qian, Yao; Alabdallah, Nadiyah M.; Jahan, Mohammad Shah; Fang, Xiang-Wen
ABSTRACT: Members of the SNF1-related protein kinase 2 (SnRK2) family are plant-specific serine or threonine kinases that play a pivotal role in the response of plants to abiotic stresses. Members of this plant-specific kinase family have included a critical regulator (SnRK2) of abscisic acid (ABA) response in plants. Plant organ development is governed substantially by the interaction of the SnRK2 and the phytohormone abscisic acid (ABA). Recent research has revealed a synergistic link between SnRK2 and ABA signaling in a plant's response to stress such as drought and shoot growth. SnRK2 kinases play a dual role in the control of SnRK1 and the development of a plant. The dual role of SnRK2 kinases promotes plant growth under optimal conditions and in the absence of ABA while inhibiting the growth of plants in response to ABA. In this review, we have uncovered the roles of ABA-activated SnRK2 kinases in plants, as well as their physiological mechanisms.